Fatores demográficos como determinantes da criminalidade - Hartung, Gabriel Chequer (2006)
The article shows the influence of some demographics factors of 1980 on crime in 2000. Using data of São Paulo state cities we show evidences that fertility rate, fraction of teenager motherhood and fraction of single mothers are important determinants of both violent crime and property crime